Application of 4C elements in online project-based learning to assist students' communication skills and problem-solving skills for biology subjects - Ehqa Dhabita Mohd Nasir; Denis Andrew D. Lajium (International Journal of Advanced Multidisciplinary Research and Studies, 2023)
The success of communication skills through online Project- Based Learning (PBL) can be achieved when students are able to express opinions, discuss with others to find solutions, interact, dialogue, argue based on evidence and solve a problem based on the real world. In recognition of the importance of online Project-Based Learning strategies in influencing students' communication and problem-solving skills, this paper aims to synthesize the existing relevant literature to establish a theoretical foundation of project- based learning that highlights the application of 4C elements namely communication, collaboration, creativity and critical, which focuses its influence on students’ communication skills and problem-solving skills. The study design was conducted qualitatively using purposive sampling method. Interview data, observations and documents were analyzed using the snowball method. Researchers selected the first case that met all the specified criteria to obtain concise data. The analysis was conducted on six respondents. In conclusion, project-based learning fulfills the key features of effective interventions for 21st century learning because project-based learning (PBL) is an educational model that prioritizes projects in teaching and learning which is also an instructional method that allows students to build skills and acquire knowledge through projects, cooperative learning and ‘hands on’ techniques. Through the implementation of the project, students can build knowledge and skills through the inquiry process. The integration of project-based learning strategies makes this instructional method adaptable to students of varying backgrounds, ages and levels of education.